Frequency Domain Sensors and Frequency Measurement Techniques; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Murrieta-Rico F. N.; Petranovskii V.; Sergiyenko O. Y.; Hernandez-Balbuena D.; Pestryakov A. N. Aleksey Nikolaevich; Tyrsa V. (Control and Automation Systems, Manufacturing Applications, 2015)
Title screen